Hierarchically porous ceria with tunable pore structure from particle-stabilized foams. Issue 12 (September 2020) - Zhang, Xiaoyan; Zhang, Youfei; Lu, Yuju; Zhang, Shuhao; Yang, Jinlong
Abstract: We firstly fabricated CeO2 ceramic foams with tunable structure by using particle-stabilized bubbles as template, and designed their interconnected porous structure and even hierarchically porous structure, which endows them the penetration ability for gases or liquids. Hollow spheres with single-layer shell were innovatively selected as the pore-former, which allows for the formation of open pores on the cell wall. Moreover, 3D printing CeO2 particle-stabilized foams are realized with the aid of direct ink writing, which enables the production of CeO2 ceramic foams with complex shape. Highly porous CeO2 with relatively high compressive strength have been fabricated, the porosity of which varies from 81.0% to 92.0% while their excellent compressive strength ranges from 5.0 MPa to 20.0 MPa. Attributed to the hierarchical porous structure, uniform pore size distribution as well as densely assembled cell wall, 3D printing CeO2 ceramic foams possess superior mechanical performance at high porosity level.